2019
DOI: 10.1002/ajp.23037
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive cardiac psychophysiology as a tool for translational science with marmosets

Abstract: The importance of marmosets for comparative and translational science has grown in recent years because of their relatively rapid development, birth cohorts of twins, family social structure, and genetic tractability. Despite this, they remain understudied in investigations of affective processes. In this methodological note, we establish the validity of using noninvasive commercially available equipment to record cardiac physiology and compute indices of autonomic nervous system activity -a major component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…In their study, they reported this sAA activity as negligible, but this is relative to 21 other mammalian species that express higher sAA levels. Previous studies have examined SNS reactivity in marmosets, but none have considered sAA reactivity in their measurements (Honda et al, 2013; Mikheenko et al, 2010; Murphy et al, 2019). In human studies, sAA levels return close to baseline values within 15–30 min of stress, albeit slightly higher (Almela et al, 2011; Kang, 2010; Nater et al, 2006; Strahler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they reported this sAA activity as negligible, but this is relative to 21 other mammalian species that express higher sAA levels. Previous studies have examined SNS reactivity in marmosets, but none have considered sAA reactivity in their measurements (Honda et al, 2013; Mikheenko et al, 2010; Murphy et al, 2019). In human studies, sAA levels return close to baseline values within 15–30 min of stress, albeit slightly higher (Almela et al, 2011; Kang, 2010; Nater et al, 2006; Strahler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Eye-tracking can also be used non-invasively in animals to give measures of attention to videos or photos with affective content (Ryan et al, 2019;Yorzinski et al, 2013). Autonomic tools also give us a non-invasive window into the internal affective lives of animals (Murphy et al, 2019).…”
Section: Technological Frontiers In the Study Of Animal Affectmentioning
confidence: 99%
“…It displays a close genetic proximity to humans compared to more commonly used rodent species and has a low zoonotic potential [7,8]. This animal species is already established in a variety of research areas like inter alia neurological research, behavioral research, and stem cell research [9][10][11][12][13][14][15], and the recently discovered possibility to generate transgenic animals broadened its potential use even further [16]. In contrast to larger, longer-lived primate species, the common marmoset exhibits a fast gestational period and, thereby, might be advantageous to other NHP models.…”
Section: Introductionmentioning
confidence: 99%